Study on flexural cracking characteristics of polypropylene fiber reinforced concrete beams with BFRP bars - Huayi Wang; Ming Zhou; Bingyan Wei; Chao Wu; Zhiyi Tang; Sitian Zhang; Jia He (Case Studies in Construction Materials)
Concrete beams reinforced with BFRP bars have problems such as low stiffness, wide cracks, and brittle flexural failure. Fibers can improve the cracking characteristics. One ordinary concrete BFRP beam and four PP - FRC BFRP beams were fabricated to investigate the influence of the volume ratio of PP fibers and the reinforcement ratio of BFRP on the flexural cracking characteristics of the beams. The results show that PP fibers do not change the flexural failure characteristics of BFRP beams but can increase the ultimate load (by 10.4 % - 36.6 %) and the deflection corresponding to the ultimate load (by 20.9 % - 50.6 %). PP fibers can increase the ultimate strain of coordinated deformation between the concrete in the flexural zone and BFRP bars by 8.77–12.79 times. PP fibers can significantly delay the damage of the concrete in the compression zone, increase the ultimate compressive strain by 60.6 % - 120.3 %, and raise the ductility coefficient by 76.9 % - 153.9 %. The crack height is reduced by 13.9 % - 53.3 % at the same curvature. When the flexural bearing capacity is 80 %, the average crack spacing is reduced by 6.1 % - 13.4 %. Adding PP fibers increased the torque value corresponding to a crack width of 0.8 mm by 28.4–77.6 %. According to the prediction formula for the cracking characteristics of ordinary concrete BFRP beams in GB 50608–2020, the calculation formulas for the average crack spacing and the maximum crack width of PP - FRC BFRP beams are proposed, and their prediction accuracy is better than that of the code formulas.